Assessment of Termite Species Diversity, Soil Chemical Characteristics, And Evaluation of Phytochemicals as Edible Termite Attractants - Ameka, Caleb Mikhali (JOOUST, 2022)
Termites are social insects that live in colonies underground. Globally, there are 3000 species, of which 39% are found in Africa. Termites are used as food and feed in most communities of the world. In Kenya, termites are consumed by many communities, especially in the western region. Termite species diversity across different parts of the Luanda sub-County needs to be established as there are many edible and non-edible species in the area. This study envisaged to assess the species diversity of termites in Luanda sub-County, analyse their habitat, soil chemical characteristics and evaluate plant derived phytochemicals used as termite attractants. Termites were sampled in Luanda sub-county using the line transect method. The collected soldier termites were preserved in tubes containing 70% Ethanol. The preserved samples were taken to the National Museums of Kenya for morphological and molecular identification up to species level. The soils in each termite habitat were collected and analysed to determine each habitat's soil chemical characteristics. Eucalyptus stems, bamboo, Grevillea robusta, Maize and sugarcane were evaluated for the presence of phytochemicals that attract termites to feed. Choice test bioassays were done to determine the response of termites to different crude phytochemicals extracted from these plants. Species richness of each habitat was analyzed for diversity (Shannon-Wiener) index and Simpson index using Vegan package version 1.16-32 in R. The differences in species composition and diversity of termites in different counties and soil chemical characteristics as well as termite phytochemical attraction bioassay was analyzed using one-way ANOVA. Morphological identification recorded seven species, while molecular identification recorded four termite species in the study area. The results of this study showed that the Shannon diversity index H was 0.3606 while Simpson index D was 0.20644, which implied a high species diversity of termites in Luanda sub-County. There was a significant difference in the soil Zinc levels for all the termite species excluding Macrotermes sp1. Feed choice bioassay revealed that termites were attracted to various feed substrates p<0.05. Termite attraction to crude plant extracts was highly significant p<0.05. This study will inform food security experts on the status of termite’s species richness and evenness in their natural ecosystem and identify plants, which attracts termites to forage, thus increase their productivity during mass harvesting for food and feed.
Keywords: Termite Species; Soil Chemical Characteristics; Phytochemicals; Edible Termite